Pelatihan Kader Kesehatan dalam Penemuan Kasus Pasien Tuberkulosis Sensitif Obat di Wilayah Puskesmas Bandarharjo Semarang - Aryani, Lenci; Isworo, Slamet; Triyono, Agus; Handayani, Sri (Jurnal Abdimas Jatibara, 2025)
Health cadres play a crucial role in detecting various health cases in the community, including tuberculosis. Tuberculosis is among the most highly transmitted diseases in Semarang City, requiring a consistent approach to case management. Health cadres serve as the frontline in identifying and supporting the treatment of tuberculosis cases. Therefore, this community engagement activity involved training health cadres on tuberculosis, covering topics such as transmission, symptoms, diagnosis, treatment, and the side effects of TB medication. The training lasted for three hours and was conducted in the teleconference room of the Faculty of Health Science at Universitas Dian Nuswantoro. A pretest was administered to assess the cadres baseline knowledge, with a score of 67 answering correctly. After the training (post-test), correct responses increased to score 75,46. These results indicate that the training improved the cadres knowledge, which is essential for supporting tuberculosis prevention efforts and reducing the incidence of new cases in the community.